Characterization of in vitro haploid and doubled haploid Chrysanthemum morifolium plants via unfertilized ovule culture for phenotypical traits and DNA methylation pattern - Wang, Haibin; Dong, Bin; Jiang, Jiafu; Fang, Weimin; Guan, Zhiyong; Liao, Yuan; Chen, Sumei; Chen, Fadi (Frontiers in Plant Science, 2014)
Chrysanthemum is one of important ornamental species in the world. Its highly heterozygous state complicates molecular analysis, so it is of interest to derive haploid forms. A total of 2,579 non-fertilized chrysanthemum ovules pollinated by Argyranthemum frutescens were cultured in vitro to isolate haploid progeny. One single regenerant emerged from each of three of the 105 calli produced. Chromosome counts and microsatellite fingerprinting showed that only one of the regenerants was a true haploid. Nine doubled haploid derivatives were subsequently generated by colchicine treatment of 80 in vitro cultured haploid nodal segments. Morphological screening showed that the haploid plant was shorter than the doubled haploids, and developed smaller leaves, flowers and stomata. An in vitro pollen germination test showed that few of the haploid's pollen were able to germinate and those which did so were abnormal. Both the haploid and the doubled haploids produced yellow flowers, whereas those of the maternal parental cultivar were mauve. Methylation-sensitive amplification polymorphism (MSAP) profiling was further used to detect alterations in cytosine methylation caused by the haploidization and/or the chromosome doubling processes. While 52.2% of the resulting amplified fragments were cytosine methylated in the maternal parent's genome, the corresponding proportions for the haploid's and doubled haploids' genomes were, respectively, 47.0% and 51.7%, demonstrating a reduction in global cytosine methylation caused by haploidization and a partial recovery following chromosome doubling.